y= cost of the bag of jaw breakers

z= cost of the bag of caramels

cost of the bag of gummy bears equals the cost of the bag of jaw breakers + .28 cents

now rewrite the equation in terms of x (the variable you are trying to solve for) now you have an equation that shows the cost of the bag of jaw breakers equals the cost of the bag of gummy bears minus .28 cents

cost of the bag of gummy bears equals the cost of the bag of caramels minus .13 cents

now rewrite that equation in terms of xnow you have an equation that states the cost of the bag of caramels equals the cost of the bag of gummy bears plus .13 cents

x + x - .28 + x + .13 = 6.39

3x - .15 = 6.39

3x = 6.54

x = 2.18